Strategi Distribusi Apollo Audio Dalam Mengatasi Kerusakan Dan Layanan Untuk Meningkatkan Kepuasan Konsumen - Wicaksono Indarto, Andre (Jurnal Etnik: Ekonomi-Teknik, 2022)
Buying and selling activities are activities that become a means to meet human needs, be it the needs of clothing, food, and housing. Because these three things are basic needs that must be met by each individual. UD Apollo must always think that every object of sale and purchase must be in good condition and quality, so that consumers are not disappointed or feel disadvantaged. Buying and selling does not only apply between regions, but between regions. In the distribution process of Apollo audio sending goods to various cities in Indonesia, Apollo audio has risks that arise in the distribution process, namely goods that are damaged due to shipping when the goods arrive to consumers and this problem has also often occurred in the distribution process of Apollo audio. The background above explains that selling used audio online has a high risk of damage due to shipping and it is related to customer satisfaction, but there are still many consumers who are still active in shopping for used audio. The aim of the research is to find out what distribution strategies are appropriate in overcoming damage and services to increase customer satisfaction. This type of research is qualitative research. The population of this study are all consumers who have purchased products at Apollo audio. The research method used in this research is to use interviews. The number of respondents used in this study were 5 respondents. The data collection technique used in this research is triangulation. The results of this study obtained that there are several distribution strategies of Apollo audio in overcoming damage and services to increase customer satisfaction, namely: (1) Strategy in distribution selection. (2) Packaging procedure strategy. (3) Good and effective complaint handling strategy